2019
DOI: 10.1016/j.nuclphysb.2019.114722
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and weak cosmic censorship conjecture in Reissner-Nordström anti-de Sitter black holes with scalar field

Abstract: The thermodynamics and weak cosmic censorship conjecture in Reissner-Nordström anti-de Sitter black holes are investigated by the scattering of the scalar field. The first law of thermodynamics in the non-extremal Reissner-Nordström anti-de Sitter black hole is recovered by the scattering. The increase of the horizon radius indicates that the singularity is not naked in this black hole. For the near-extremal and extremal black holes, the validity is tested by the minimum values of the function f at their final… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Different from [60], we have chosen another quantum gravity model, GUP, to study the second law of thermodynamics and the weak cosmic censorship conjecture in the normal and extended phase space. When β → 0, f ( β 0 4πT [P r (r + )] 2 mp ) → 1 and the GUP deformed case reduces to the usual case, and our result is consistent with that in [27,29,34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Different from [60], we have chosen another quantum gravity model, GUP, to study the second law of thermodynamics and the weak cosmic censorship conjecture in the normal and extended phase space. When β → 0, f ( β 0 4πT [P r (r + )] 2 mp ) → 1 and the GUP deformed case reduces to the usual case, and our result is consistent with that in [27,29,34].…”
Section: Discussionsupporting
confidence: 90%
“…However, considering the back reaction and self-force effects, the study suggests that the weak cosmic censorship conjecture may be still satisfied [18][19][20][21][22][23]. Since there is a lack of universal evidence for the weak cosmic censorship conjecture, its validity has been tested in various black holes [24][25][26][27][28][29][30][31]. Recently, the validity of the weak cosmic censorship conjecture through absorption of charged particles in extended phase space has been tested in extended phase space, where the cosmological constant is treated as thermodynamic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Since the motion of a massive particle outside the event horizon should be future directed and time-like, we have chosen the future directed solution dt/dτ > 0, which is equivalent to the requirement δE > − g 03 g 33 δJ.…”
Section: Weak Cosmic Censorship Conjecture For Kerr-taub-nut Blackmentioning
confidence: 99%
“…Further exploration of Gwak indicates that both extremal and near-extremal Kerr-(anti) de Sitter black holes cannot be over-spun by classical fields [30]. Following this line, a series of works have shown that BTZ black holes [31,32], four-dimensional and higher-dimensional charged AdS black holes [33,34] cannot be over-spun or over-charged by classical test fields. These results suggest that the weak cosmic censorship conjecture is preserved in classical wave scattering process.…”
Section: Introductionmentioning
confidence: 95%
“…Our motivation is to explore how f (r min ) moves as a charged particle is absorbed by the Gauss-Bonnet AdS black hole. For the initial state is a black hole, f (r min ) satisfies the following conditions [47,48,49,50,51,52] f (M, Q, α, l, r)| r=r min ≡ f min = δ ≤ 0,…”
Section: Weak Cosmic Censorship Conjecture In the Normal Phase Spacementioning
confidence: 99%